The model of brittle matrix composites for distribution of steel fibres - Głodkowska, Wiesława; Kobaka, Janusz (Journal of Civil Engineering and Management, 2012)
The paper deals with the distribution of steel fibres in the mineral composite of fine aggregate. The authors have proposed the distribution of steel fibres in a composite space model based on statistical grounds. The model provides for the randomness of fibre distribution in composite space in accordance with the adopted probability distribution. The developed model has been experimentally verified. The results concerning the distribution of steel fibres in mineral com- posite have been obtained from the statistical model and compared with those of the model frequently applied by other au- thors on the basis of geometric grounds. Good compatibility of steel fibre distribution for a description of both models has been ascertained. As the amount of fibres influences the strength of composite tensile, the relationship between the above introduced feature and the quantity of fibres in the cross-section located nearby tensile failure surface has been developed with reference to the experimental tests.Plieninių fibrų pasiskirstymo kompozituose su trapiomis matricomis modelisSantrauka. Straipsnyje analizuojamas plieninių fibrų pasiskirstymas kompozite su mineraliniais užpildais. Autoriai pasiūlė plieninių fibrų pasiskirstymo kompozite modelį, grįstą statistine analize. Fibrų pasiskirstymas matricoje nagrinėjamas kaip atsitiktinis dydis, pasiskirstęs pagal tikimybinį skirstinį. Modelis yra eksperimentiškai patikrintas: plieninių fibrų pasiskirstymas kompozito matricoje pagal siūlomą statistinį modelį buvo palygintas su kitų autorių tyrimų rezultatais, taikant modelius, grįstus geometriniais pagrindais. Gauti rezultatai sutampa gerai. Kadangi plieninių fibrų kiekis turi įtakos kompozito tempiamajam stipriui, pateikta eksperimentiniais tyrimais pagrįsta priklausomybė tarp fibrų kiekio ir kompozito tempiamojo stiprio.Reikšminiai žodžiai: mineralinis kompozitas, fibros, fibrų pasiskirstymas, modelis, analizė.